Decision Support System for Purchasing Speaker Monitor Home Recording Using Fuzzy Multiple Attribute Decision Making - Wahyu Widodo; Adhitya Pratama (Fakultas Teknik Universitas Bhayangkara, 2023)
Technological developments in the field of music are currently experiencing progress, including the formation of computer-based recording, namely the Digital Audio Workstation (DAW). Monitor speakers are one of the most important components of a DAW. A good selection of monitor speakers can support the quality of sound produced by a home recording or recording service provider. The many variations and specifications of monitor speakers on the market make it difficult for users to choose based on four criteria: price, response frequency, design criteria, and power output. So it is necessary to make an application that can determine recommendations for purchasing monitor speakers by applying the Fuzzy Multiple Attribute Decision Making Algorithm. The results obtained in this study show that of the five alternative monitor speakers, KRK ROKIT G4 5 has the highest alternative preference rating of 2.2,5 so it can be used as a reference monitor speaker for home recording.